Japan and Malaysian development in the shadow of the rising sun - K.S., Jomo (Routledge, 1994)
The Japanese presence in Southeast Asia is treated variously with either suspicion or encouragement. Japan and Malaysian Development critically assesses different dimensions of Japan-Malaysia economic relations. The work presents a balanced collection of essays examining Japanese involvement in Malaysia. The volume also discusses the impact and consequences of Malaysian Prime Minister Mahathir's 'Look East' policy, which advocated greater emphasis on trading relations with Japan.